Modified COVID-19 Mortality Scoring as a Mortality Prognostic in COVID-19 Patients - Rahmadani Puji Lestari; Benedictus Hangga Harinawantara; Khoironi Rachmad Damarjati; Purwadi Sujalmo (Academic Hospital Journal, 2022)
Background: The number of patients infected with COVID-19 was increasing. The COVID-19 clinical presentation varies from asymptomatic, mild, moderate, severe, and critical. Mortality rates increase with morbidity and disease severity. This study aimed to develop a prognostic intrahospital mortality scoring named "Modified COVID-19 Mortality Scoring".Methods: A retrospective cohort study was conducted on COVID-19 inpatients at the UGM Academic Hospital during November 2020-March 2021. Data were obtained from electronic medical records. Clinical and laboratory parameters were taken at the time of admission.Results: The study involved 413 patients, including 50 subjects who died from COVID-19 and 363 survivors. The final stage of multivariate analysis resulted in some variables; age≥55 years, history of stroke, qSOFA score≥2, d-dimer≥1500 ng/mL, absolute neutrophil count (ANC)≥5,000 cells/uL, and absolute lymphocyte count (ALC)<1,000 cells /uL affected intrahospital mortality (p<0.050). In the scoring model, the d-dimer≥1500 ng/mL was worth 2 points, and each remaining variable was worth 1 point. The score had a strong predictive ability with an area under the ROC curve, 0.814(95%CI=0.757–0.871). The sensitivity and specificity of the score was 76%, with a cutoff point score of 3, an OR of 10,357 (95%CI=5.179-20,710, p=0.000). Moreover, the probability scores of 3, 4,5,6,7 were 18%, 33%, 53%, 72%, and 85%.Conclusion: The existence of a scoring system is expected to help identify COVID-19 inpatients who have a higher risk of death so that stricter monitoring and early intervention can be carried out.